Androgen-induced cerebral venous sinus thrombosis in a young body builder: case report - Sahraian, Mohammad Ali (BioMed Central, 2004)
BACKGROUND: Cerebral venous sinus thrombosis is an infrequent disease with a variety of causes. Pregnancy, puerperium, contraceptive pills and intracranial infections are the most common causes. The patient may present with headache, focal neurological deficits and seizures. The clinical outcome is highly variable and treatment with heparin is advised. CASE PRESENTATION: The patient is a 22 year old male who presented with headache, repeated vomiting and papilledema. He was a bodybuilder doing exercise since 5 years ago, who had used nandrolone decaonoate 25 milligrams intramuscularly during the previous 5 months. Brain MRI and MRV showed superior sagital and transverse sinus thrombosis and extensive investigations did not reveal any known cause. CONCLUSIONS: We suggested that androgen was the predisposing factor in our patient. Androgens may increase coagulation factors or platelet activity and cause arterial or venous thrombosis. As athletes may hide using androgens it should be considered as a predisposing factor for thrombotic events in such patients.